Cognitive Correlates of the Covariance in Reading and Arithmetic Fluency: Importance of Serial Retrieval Fluency. Issue 4 (10th July 2019) - Koponen, Tuire; Eklund, Kenneth; Heikkilä, Riikka; Salminen, Jonna; Fuchs, Lynn; Fuchs, Douglas; Aro, Mikko
Abstract : This study examines the core predictors of the covariance in reading and arithmetic fluency and the domain‐general cognitive skills that explain the core predictors and covariance. Seven‐year‐old Finnish children ( N  = 200) were assessed on rapid automatized naming (RAN), phonological awareness, letter knowledge, verbal counting, number writing, number comparison, memory skills, and processing and articulation speed in the spring of Grade 1 and on reading and arithmetic fluency in the fall of Grade 2. RAN and verbal counting were strongly associated, and a constructed latent factor, serial retrieval fluency (SRF), was the strongest unique predictor of the shared variance. Other unique predictors were phonological awareness, number comparison, and processing speed. Findings highlight the importance of SRF in clarifying the relation between reading and arithmetic fluency.